Legislation study methods to save the environment - Tommy Hendra Purwaka (Universitas Pakuan, 2021)
This paper provides an overview of the different methods available to critical analyse existing environmental laws and their potential for achieving genuine environmental change. It highlights how misinterpretation of the substance of laws and regulations, malfunction of legislation, disagreement among stakeholders in the application of available legal instruments and the absence of monitoring, control, and surveillance can result in inappropriate application of laws, contributing to misuse of natural resources and the environment decline. It outlines four methods of legal analysis to review the efficacies of existing laws to identify areas potential for legal reform these are; analysis of legal content, legal functions, legal instruments, and legal monitoring, control and surveillance.Makalah ini memberikan gambaran umum tentang berbagai metode yang tersedia untuk menganalisis secara kritis undang-undang lingkungan yang ada dan potensinya untuk mencapai perubahan lingkungan asli. Tulisan ini menyoroti bagaimana salah tafsir substansi undang-undang dan peraturan, ketidak berfungsinya undang-undang, ketidak sepakatan di antara para pemangku kepentingan dalam penerapan instrumen hukum yang tersedia dan tidak adanya pemantauan, kontrol, serta pengawasan, yang dapat mengakibatkan penerapan undang-undang yang tidak tepat, berkontribusi pada penyalah gunaan sumber daya alam, dan penurunan kualitas lingkungan. Ini menguraikan empat metode analisis hukum untuk meninjau efektivitas hukum yang ada untuk mengidentifikasi bidang yang berpotensi untuk reformasi hukum; analisis muatan hukum, fungsi hukum, perangkat hukum, serta pemantauan hukum, kontrol dan surveillance.